2002
DOI: 10.1089/105072502753522310
|View full text |Cite
|
Sign up to set email alerts
|

Tie-2 and Angiopoietin-1 Expression in Human Thyroid Tumors

Abstract: Tie-2 is an endothelial cell-specific receptor tyrosine kinase involved in vascular maturation and remodeling. Although its expression is considered to be restricted to vascular endothelial cells and hematopoietic progenitors, our immunohistochemical and in situ hybridization studies showed that Tie-2 and its ligand, angiopoietin (Ang)-l were expressed not only in benign and malignant human thyroid tumor cells but also in hyperplastic regions of adenomatous goiter. To confirm the expression in these tissues fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 15 publications
0
35
0
Order By: Relevance
“…A receptor-mediated response is likely given that Tie2 expression was induced by hyperoxia 59 and Tie2 has been detected on normal and transformed epithelial cells. [66][67][68] Furthermore, we detected Tie2 mRNA in the MLE cells used for our in vitro studies. 59 Importantly, we found Ang2-mediated hyperoxia-induced increases in initiator and effector caspases, namely caspase-3, -8 and -9.…”
Section: Angiopoietin 2 and Hali In Animal Modelsmentioning
confidence: 99%
“…A receptor-mediated response is likely given that Tie2 expression was induced by hyperoxia 59 and Tie2 has been detected on normal and transformed epithelial cells. [66][67][68] Furthermore, we detected Tie2 mRNA in the MLE cells used for our in vitro studies. 59 Importantly, we found Ang2-mediated hyperoxia-induced increases in initiator and effector caspases, namely caspase-3, -8 and -9.…”
Section: Angiopoietin 2 and Hali In Animal Modelsmentioning
confidence: 99%
“…Tie2 expression occurs, and is partially maintained, during differentiation in human neural stem cells (7), but not in mature neurons (8). Dysregulated Tie2 expression has also been observed in several tumor tissues, including oral squamous cell carcinoma, breast, gastric, leukemia and thyroid cancer (9)(10)(11)(12)(13). These studies revealed that Tie2 expression is associated with the identification and prognosis of these cancer types (12).…”
Section: Introductionmentioning
confidence: 99%
“…Daly et al (6) revealed that Ang2 functions as a Tie2 agonist in tumor models, limiting the effects of VEGF inhibition (6). Mitsutake et al (13) revealed that Tie-2 and its ligand Ang1 were expressed in benign and malignant human thyroid tumor cells, as well as in hyperplastic regions of adenomatous goiter (13). However, the function and mechanism of the Ang1/Tie2 pathway in the proliferation and migration of PTC cells remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The coexpression of Ang-1, -2 and -4 and Tie-1 and -2 has been reported in tumor cells, suggesting the presence of an autocrine and/or a paracrine angiopoietin/Tie growth pathway in solid tumors [35][36][37][38] . Angiopoietins (Angs) also have been shown to play a role in the proliferation and/or differentiation of stromal tumors and normal mesenchymal cells [41,42] .…”
Section: Discussionmentioning
confidence: 99%
“…Coexpression of angiopoietin and its receptor, either Tie-1 or Tie-2, has been reported in tumor cells, suggesting the presence of an autocrine and/or a paracrine angiopoietin/Tie growth pathway in solid tumors [34][35][36] . Further, the expression levels of angiopoietin and its receptors have been shown to correlate with progressive tumor growth and development of metastasis by many types of carcinomas [35][36][37][38] . These studies suggest that the angiopoietin pathway is involved in tumor cell growth and differentiation.…”
Section: Introductionmentioning
confidence: 99%